Histopathological Effects of Oral Administration of Nigella Sativa Hydroalcoholic Extract On Rat Digestive Tract - Mohammad Babaei; Ghasem Akbari; Amir Ali Shahbazfar (Tehran University of Medical Sciences, 2020)
Background and Aim: Nigella sativa with anti-inflammatory and antimicrobial effects is one of the most widely used medicinal plants that can be used as an alternative or adjunctive therapy due to many side effects of chemical drugs. The aim of this study was to evaluate the regenerative and protective effects of Nigella sativa from pathological point of view in rat gastrointestinal tract. Materials and Methods: This study was carried on 30 wistar male rats which were divided randomly in to 3 groups. First and second experimental groups received 400 and 800 mg/kgbw Nigella sativa extract respectively and control group received normal saline orally by gavage for 2 months. The duodenum, jejunum, ileum and proximal colon samples were collected and after fixation with formalin 10% and tissue processing, the 5 μm sections were prepared and stained by hematoxylin eosin staining. Finally, light microscopy was used to determine the histological characteristics and the length of the small and large intestinal villi in the area of the duodenum, jejunum, ileum, colon, villus width and percentage of goblet cells. Data were analyzed by SPSS software. Results: The results showed that Nigella sativa significantly increased the length of the villi in duodenum, jejunum and ileum. The width of the villi and the percentage of goblet cells were also increased. Conclusion: Based on the results, it can be concluded that the Nigella sativa causes enhancement of food absorption by increasing the length of villi and has protective effects.